Impacto de las estrategias Montessori en la autonomía infantil: un estudio preexperimental - Portales Rosas, Debora Stephania; Rodríguez Nieto, Ingrid Milagritos (LACCEI, 2025)
This article presents the results of a pre-experimental study aimed at analyzing the influence of strategies based on the Montessori method on children’s autonomy. The intervention was carried out with four-year-old children, applying an observation guide before and after implementing activities designed to promote decision-making, self-management, and problem-solving. The data were processed using the Student t-test for related samples, obtaining a significant difference (t = value obtained, p = 0.000) in the general autonomy variable. The findings confirm notable progress: before the intervention, 62% of the children showed a low level of autonomy, while after applying the Montessori strategy, 85% achieved a high level. These results demonstrate that the Montessori methodology represents an effective tool for fostering independence and self-confidence from early childhood.